L'Immagine Provocata - Carluccio, Luigi; Biennale di Venezia (Milano : Gruppo editoriale Electa s.p.a, 1979)
Giacomelli, Mario ; Avigdor, Giorgio ; Masera, Piero ; Zennier, Italo ; Fontana, Franco ; Mezzano, Elsa ; Ghirri, Luigi ; Capaldi, Gianni ; Spada, Francesco ; Plessi, Fabrizio ; Saba, Isio ; Rondelli, Lia ; Patella, Luca
La Biennale di Venezia
Italiaans
kunstcatalogus